The Choice of Ideology and Everyday Decisions - Burs, Carina; Gries, Thomas; Müller, Veronika (Journal of Organizational Psychology)
Individuals strive to make decisions that are consistent with not only their consumer preferences but also their psychological needs. However, they are confronted with complex, ambiguous or even false information. Ideologies and belief systems provide guidance when processing and evaluating information and give a coherent and comprehensible interpretation of reality. The first question is: why is an individual attracted to a particular ideology? Individuals choose ideologies that resonate with their subjective psychological needs and preferences. Second, how do individuals search for ideologies and find out which suit them best? We model an individual’s sequential information search for the best matching ideologies by applying Bayesian learning and utility optimization. Additional information enhances utility by reducing uncertainty. As a search is costly, the process may stop once an individual adopts an ideology even if the information set remains incomplete. Third, once they have chosen a particular ideology, individuals adhere to its rules and norms when making everyday decisions. Consumers not only physically consume, but they also act in accordance with their psychological needs.
Keywords: Economics; Ideology; Decision-making

The Problems of Base/Superstructure and Ideology in the Works of Stuart Hall, Georg Lukács, and Raymond Williams - Fuchs, Christian (The Communication Review.)
We live in times of deep crisis. General crises of society often are accompanied by ideological struggles. Given this context, it is important that social theory reinvigorates the analysis of ideology. For doing so, it makes sense to engage with classical theories of ideology. This paper contributes to this task. It asks: How are the economic and the non-economic related? What is ideology? This article deals with the base/superstructure problem and the problem of ideology via an engagement with selected aspects of Stuart Hall’s, Georg Lukács’s and Raymond Williams’s works. The commonality of Hall’s, Lukács’s and Williams’s thoughts that makes a joint engagement with their works feasible is that they all three dealt with aspects of culture from a critical theory perspective and are in one way or another representatives of Cultural Marxism. While Lukács’s works and Cultural Studies are often presented as conflicting approaches, this paper shows that concerning the question of how the economic and the non-economic are related and how we can think of ideology, the approaches of Lukács, Williams, and Hall complement each other, which allows critical theories of culture to draw on all three approaches and to combine elements from them in a synergistic manner. There are parallels between Williams’, Hall’s, and Lukács’s solutions to the base/superstructure problem. Williams argues that the economic exerts pressures on and sets limits to the non-economic. Hall writes that the economic determines the non-economic in the first instance. Lukács argues that the economic circumscribes subjectivity and the non-economic.
Keywords: base and superstructure; culture; economy and culture; Georg Lukács; ideology; Raymond Williams; Stuart Hall

An Economic Theory of 'Destabilization War' - Gries, Thomas; Haake, Claus-Jochen
While Islamic State is the most present example, it is a fact that in many places around the globe, throughout history initially small groups have tried to challenge and destabilize or even overthrow governments by means of terrorist and guerrilla strategies. Therefore, we answer two questions. Why does a small group of insurgents believe it can overthrow the government by turning violent, even if the government is clearly superior? And how does a conflict develop into terrorism, a guerilla war, or a major conventional civil war, or is resolved peacefully? We develop a formal model for rebels and government and derive optimal choices. Further, we focus on three elements as important ingredients of a "destabilization war". All three of these - large random events, time preference (which we relate to ideology), and choice of duration of fight - are rarely considered in formal conflict theory. We can answer the above two questions using game theory analysis. First, insurgents rise up because they hope to destabilize through permanent challenging attacks. In this context, large randomness is an important ally of rebels. While each individual attack may have a low impact, at some point a large random event could lead to success. Hence, the duration of activities is a constitutive element of this kind of armed conflict. Patience (low time preference), which may reflect rebels' degree of ideological motivation, is crucial. Second, the mode of warfare or the conflict resolutions that develop are generally path-dependent and conditioned on the full set of options (including compromise). Various conditions (level of funding, ease of recruitment, access to weapons) influence different modes of warfare or a peaceful compromise in a complex way.
Keywords: terrorism; civil war; conflict duration; game theory; stochastic process; ideology